Using Interactive Learning Modules to Teach Value-Based Health Care to Health Professions Trainees Across the United States. (September 2019) - Moriates, Christopher; Valencia, Victoria; Stamets, Sara; Joo, Joseph; MacClements, Jonathan; Wilkerson, LuAnn; Nelson, Elizabeth A.; Bozic, Kevin; Cox, Susan M.
Abstract : Problem: Despite prominent calls to incorporate value-based health care (VBHC) into medical education, there is still a global need for robust programs to teach VBHC concepts throughout health professions training. Approach: In June 2017, Dell Medical School released the first collection (three modules) of a set of free interactive online learning modules, which aim to teach the basic foundations of VBHC to health professions learners at any stage of training and can be incorporated across diverse educational settings. These modules were designed by an interprofessional team based on principles of cognitive engagement for active learning. Outcomes: From June 2017 to September 2018, the website received 130, 098 pageviews from 8, 546 unique users (2, 072 registered users), representing 45 states in the United States and 10 foreign countries. As of October 15, 2018, 568 (27%) of registered users completed modules 1–3. Five-hundred thirty-five of these users completed a survey (94% response rate). Nearly all (484/535; 90%) reported overall satisfaction with the curriculum, 522/535 (98%) agreed "after completing the modules, I can define value in health care, " and 520/535 (97%) agreed "after completing the modules, I can provide examples of low- and high-value care." Second-year Dell Medical School students reported that they have incorporated value into their clinical clerkships (e.g., by discussing VBHC with peers [43/45; 96%]) as a result of completing the modules. Next Steps: Future plans for the curriculum include the release of additional modules, more robust knowledge assessment, and an expanded learning platform that allows for further community engagement.